Metabolomic markers of antepartum depression and suicidal ideation - Mitro, Susanna D. (2020)
Background: Recent analyses have described metabolomic markers for depression and suicidal ideation in non-pregnant adults. We examined the metabolomic profile of antepartum depression and suicidal ideation during mid-pregnancy, a time of high susceptibility to mood disorders. Methods: We collected fasting blood from 100 pregnant Peruvian women and profiled 307 plasma metabolites using liquid chromatography-mass spectrometry. We used the Patient Health Questionnaire 9 to define antepartum depression (score ≥ 10) and suicidal ideation (having thoughts that you would be better off dead, or of hurting yourself). Logistic regression was used to calculate odds ratios (ORs). Results: Three triacylglycerol metabolites (C48:5 triacylglycerol [OR = =1.89; 95% confidence interval (CI): 1.14–3.14], C50:6 triacylglycerol [OR = =1.88; 95%CI: 1.13–3.14], C46:4 triacylglycerol [OR = =1.89; 95%CI: 1.11–3.21]) were associated with higher odds of antepartum depression and 4 metabolites (betaine [OR = =0.56; 95%CI:0.33–0.95], citrulline [OR = =0.58; 95%CI: 0.34–0.98], C5 carnitine [OR = =0.59; 95%CI: 0.36–0.99], C5:1 carnitine [OR = =0.59; 95%CI: 0.35–1.00]) with lower odds of antepartum depression. Twenty-six metabolites, including 5-hydroxytryptophan (OR = =0.52; 95%CI: 0.30–0.92), phenylalanine (OR = =0.41; 95%CI: 0.19–0.91), and betaine (OR = =0.53; 95%CI: 0.28–0.99) were associated with lower odds of suicidal ideation. Limitations: Our cross-sectional study could not determine whether metabolites prospectively predict outcomes. No metabolites remained significant after multiple testing correction; these novel findings should be replicated in a larger sample. Conclusions: Antepartum suicidal ideation metabolomic markers are similar to markers of depression among non-pregnant adults, and distinct from markers of antepartum depression. Findings suggest that mood disorder in pregnancy shares metabolomic similarities to mood disorder at other times and may further understanding of these conditions’ pathophysiology.